Digitalization of the economy: an overview of trends in Kazakhstan - Myrzhykbayeva, A.B.; Vystavkina, A.A.; Taizhanovan, S.E. ("Акад. Е.А. Бөкетов ат. Қарағанды ун-ті" КЕАҚ баспасы, 2022)
the article describes the directions of development of digital technologies in industrial and IT companies within the framework of the Industry 4.0 program.
Keywords: digitalization; technologies; program "Digital Kazakhstan"; information systems